Kant in "pravica do laži" - Zupančič Žerdin, Alenka (Filozofski vestnik, 1993)
Text offers interpretation of controversy between Kant and Constant started by Constant and responded by Kant with short essay "On the Presumed Right to Lie out of Philanthropy". Authoress treats the question of "Right to Lie" on one side through the problematic of right/law and on the other through ethics
Keywords: ethics; etika; filozofija; Kant, Immanuel, 1724-1804; law; laž; philosophy; pravo; subjekt